2020
DOI: 10.3390/ijms21082736
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11 Non-Canonical Inflammasome: Emerging Activator and Regulator of Infection-Mediated Inflammatory Responses

Abstract: Inflammation is a body's protective mechanism to eliminate invading pathogens and cellular damaging signals. The inflammatory response consists of two main consecutive steps-a priming step preparing the inflammatory responses and a triggering step boosting the inflammatory responses. The main feature of the triggering step is the activation of the inflammasome, an intracellular multiprotein complex facilitating the inflammatory responses. The regulatory roles of 'canonical' inflammasomes in the inflammatory re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 42 publications
(65 reference statements)
0
32
0
3
Order By: Relevance
“…However, the relative contribution to the pathogenesis of endotoxemia or bacterial sepsis is unclear [74]. Studies in mice have highlighted the involvement of CASP11-dependent inflammation in a wide spectrum of inflammatory diseases, such as rheumatoid arthritis, inflammatory bowel disease and neurodegenerative diseases [75]. Although there might be considerable redundancies in the functions of CASP4 and CASP5, our results raise the interesting possibility that inhibition of TYK2 may be an attractive therapeutic target for the treatment of CASP5-driven diseases.…”
Section: Discussionmentioning
confidence: 82%
“…However, the relative contribution to the pathogenesis of endotoxemia or bacterial sepsis is unclear [74]. Studies in mice have highlighted the involvement of CASP11-dependent inflammation in a wide spectrum of inflammatory diseases, such as rheumatoid arthritis, inflammatory bowel disease and neurodegenerative diseases [75]. Although there might be considerable redundancies in the functions of CASP4 and CASP5, our results raise the interesting possibility that inhibition of TYK2 may be an attractive therapeutic target for the treatment of CASP5-driven diseases.…”
Section: Discussionmentioning
confidence: 82%
“…Caspase-11 non-canonical inflammasomes are activated in response to intracellular LPS by the direct interaction between CARD of caspase-11 and the lipid A moiety of LPS. Upon activation, LPS-caspase-11 complexes are oligomerized, and caspase-11 inflammasomes induce the proteolytic processing of GSDMD, leading to N-GSDMD-mediated membrane pore formation and pyroptosis [ 11 , 12 , 14 , 22 ]. Interestingly, recent studies have demonstrated the functional crosstalk between the caspase-11 non-canonical and NLRP3 inflammasomes during inflammatory responses.…”
Section: Inflammasome-induced Inflammatory Responsesmentioning
confidence: 99%
“…Interestingly, recent studies have demonstrated the functional crosstalk between the caspase-11 non-canonical and NLRP3 inflammasomes during inflammatory responses. Caspase-11 activates the NLRP3 inflammasome by inducing K + efflux [ 12 , 15 , 42 , 43 ], and this causes proteolytic activation of caspase-1, leading to caspase-1-mediated maturation and secretion of IL-1β and IL-18, and N-GSDMD-mediated pyroptosis [ 12 , 15 , 22 , 44 , 45 ], which implies that canonical and non-canonical inflammasomes cooperate to induce inflammatory responses and that there may be functional crosstalk between non-canonical caspase-11 and other types of canonical inflammasomes during these responses.…”
Section: Inflammasome-induced Inflammatory Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first review article by Yi summarized and discussed the current studies exploring the activation mechanisms and the regulatory roles of non-canonical inflammasomes, such as mouse caspase-11 and human caspase-4 and caspase-5 non-canonical inflammasomes in the inflammatory response and human diseases [ 4 ]. This review provided insight into new strategies for the development of anti-inflammatory therapeutics against infectious and inflammatory diseases via targeting non-canonical inflammasomes.…”
mentioning
confidence: 99%